Copyright and the Brain - Mark Bartholomew (Washington University Law Review, 2020)
This Article explores the intersection of copyright law, aesthetic theory, and neuroscience. The current test for copyright infringement requires a court or jury to assess whether the parties’ works are “substantially similar” from the vantage point of the “ordinary observer.” Embedded within this test are several assumptions about audiences and art. Brain science calls these assumptions into question. The substantial similarity test posits that aesthetic reactions are unmeasurable and uniform. In actuality, they can be quantified and vary depending on audience and artistic medium. Neuroscience has already reconfigured the law in many areas, from tort damages to the death penalty. Now it may offer copyright law a way forward, opening up the black box of aesthetic encounters to reveal what is most salient when making the comparison at the heart of copyright infringement. Three suggested reforms—admitting expert testimony to tailor the substantial similarity test to different kinds of artistic works, using survey evidence to better understand the aesthetic responses of specialized audiences, and reordering the infringement analysis to debias judges and jurors—deploy the insights of neuroaesthetics to improve the law of copyright infringement.
Keywords: Copyright law; Neuroscience; Aesthetic decisions; Neuroaesthetics; Copyright infringement; Intellectual property